Our experience of laser iridotomy in patients with chronic angle closure glaucoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Determining the strategy of surgical treatment for chronic angle closure glaucoma (CACG) is still important.Purpose: To assess the efficacy, rates of successful intraocular pressure (IOP) lowering and the increase in anterior chamber angle for laser peripheral iridotomy (LPI) in patients with CACG.Material and Methods: We examined 31 patients (31 eyes; 18 women and 13 men) who had undergone LPI for CACG. Patient age ranged from 49 to 77 years (mean age, 64.8 ± 5.3 years). The indication for LPI was an anterior chamber angle of Shaffer grade 2 to 3 and the presence of optic neuropathy. Mean Maklakoff intraocular pressure (IOP) was 23.4 ± 1.2 mmHg.Results: Thirteen patients required surgery during the follow-up after LPI. Particularly, 10 eyes required phacoemulsification (PHACO) only, and 3 eyes, PHACO plus goniosynechialysis (GSL), because of decompensated IOP and an anterior chamber angle narrower than Shaffer grade 2 by gonioscopy. Kaplan-Meier survival analysis showed that the rates of successful IOP lowering for laser peripheral iridotomy (without the need for surgery, PHACO alone or PHACO plus GSL) at 12 months, 24 months and 36 months were 87.1%, 71.0% and 58.06%, respectively.Conclusion: The LPI is effective for opening the anterior chamber angle and reducing IOP over 6 months, but is less effective and does not allow opening the anterior chamber angle over a period exceeding 6 months. The LPI may be considered as a preparatory procedure in CACG, particularly in the presence of an acute angle-closure glaucoma attack in the fellow eye.Keywords: chronic angle closure glaucoma, laser peripheral iridotomy, gonioscopy, phacoemulification, goniosynechialysis, anterior chamber angle optical coherence tomography
Keywords: chronic angle closure glaucoma; laser peripheral iridotomy; gonioscopy; phacoemulification; goniosynechialysis; anterior chamber angle; optical coherence tomography angiography